Crosstalk between gut microbiota and host immune system and its response to traumatic injury - Ullah, Hanif; Arbab, Safia; Tian, Yali; Chen, Yuwen; Liu, Chang-qing; Li, Qijie; Li, Ka (Frontiers in Immunology, 2024)
Millions of microorganisms make up the complex microbial ecosystem found in the human gut.The immune system's interaction with the gut microbiota is essential for preventing inflammation and maintaining intestinal homeostasis. Numerous metabolic products that can cross-talk between immune cells and the gut epithelium are metabolized by the gut microbiota. Traumatic injury elicits a great and multifaceted immune response in the minutes after the initial offense, containing simultaneous pro-and anti-inflammatory responses. The development of innovative therapies that improve patient outcomes depends on the gut microbiota and immunological responses to trauma.The altered makeup of gut microbes, or gut dysbiosis, can also dysregulate immunological responses, resulting in inflammation. Major human diseases may become more common as a result of chronic dysbiosis and the translocation of bacteria and the products of their metabolism beyond the mucosal barrier. In this review, we briefly summarize the interactions between the gut microbiota and the immune system and human disease and their therapeutic probiotic formulations.We also discuss the immune response to traumatic injury.